Association between obesity and knee osteoarthritis in users of Brazilian unified national health system - Chacur, Eduardo Paul; Fidale, Thiago Montes; Limongi, Jean Ezequiel; Diniz, Fernando Leonardo; Filho, Dalton Muller Pessoa [UNESP]; Mello, Luciana da Silva [UNESP]; Oliveira, Tarley Santos; Santee, Kadija Mohamed; de LIMA, Fanny Gonçalves; Lizardo, Frederico Balbino; Neiva, Cassiano Merussi [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
Verify possible associations between obesity and knee OA in users of Brazilian Unified National Health System (Sistema Único de Saúde-SUS) of primary care network in Catalão-GO, Brazil. This is an observational study conducted in 2014 and 2015. A total of 81 volunteers from the Basic Attention Network in the city of Catalão, with body mass index (BMI) over 30 kg/m2 in both sexes, age between 40 and 60 years, and OA on radiological examination of the knee. Obesity was classified according to BMI. The diagnosis of osteoarthritis (OA) was made clinically and by radiography according to Kellgren radiological classification. The level of physical activity was assessed using the Baecke questionnaire and the Gordon Functional Classification. The volunteers underwent an anthropometric evaluation and physical examination with inspection and palpation of the joint and subsequent radiological examination of the knee. The volunteers answered a questionnaire on the level of physical activity and functional classification. Data analysis was performed using Fisher’s exact test or chi-square test was used for comparisons of two proportions. In comparisons of continuous variables, Student’s t-test or the nonparametric Wilcoxon-Mann-Whitney test was used. The level of significance was set to 5%. Practice of regular physical exercise decreases functional impairment in obese individuals with knee OA. The weight variable demonstrated a strong association with the severity of OA and degree of functionality of patients. Obesity and OA durations and lack of patient guidance are variables that may contribute to the progression of knee OA. Although the incidence among men is lower, they are more severely affected and anthropometric evaluation and physical examination are an efficacy implementations for Brazilian users of SUS.
Associação entre obesidade e osteoartrite de joelhos em usuários do sistema único de saúde Brasileiro
Keywords: Anthropometry; Obesity; Osteoarthritis; Primary health care; X-ray